Effects of physical exercise on neuromuscular junction degeneration during ageing: A systematic review - Qianjin Wang; Can Cui; Ning Zhang; Wujian Lin; Senlin Chai; Simon Kwoon‐Ho Chow; Ronald Man Yeung Wong; Yong Hu; Sheung Wai Law; Wing‐Hoi Cheung (2024)
The neuromuscular junction (NMJ) is a specialized chemical synapse that converts neural impulses into muscle action. Age-associated NMJ degeneration, which involves nerve terminal and postsynaptic decline, denervation, and loss of motor units, significantly contributes to muscle weakness and dysfunction. Although physical training has been shown to make substantial modifications in NMJ of both young and aged animals, the results are often influenced by methodological variables in existing studies. Moreover, there is still lack of strong consensus on the specific effects of exercise on improving the morphology and function of the ageing NMJ. Consequently, the purpose of this study was to conduct a systematic review to elucidate the effects of exercise training on NMJ compartments in the elderly. We conducted a systematic review using PubMed, Embase, and Web of Science databases, employing relevant keywords. Two independent reviewers selected studies that detailed NMJ changes during exercise in ageing, written in English, and available in full text. In total, 20 papers were included. We examined the altered adaptation of the NMJ to exercise, focusing on presynaptic and postsynaptic structures and myofibers in older animals or humans. Our findings indicated that aged NMJs exhibited different adaptive responses to physical exercise compared to younger counterparts. Endurance training, compared with resistance and voluntary exercise regimens, was found to have a more pronounced effect on NMJ structural remodeling, particularly in fast twitch muscle fibers. Physical exercise was observed to promote the formation and maintenance of acetylcholine receptor (AChR) clusters by increasing the recombinant docking protein 7 (Dok7) expression and stabilizing Agrin and lipoprotein receptor-related protein 4 (LRP4). These insights suggest that research on exercise-related therapies could potentially attenuate the progression of neuromuscular degeneration. Translational potential of this article: This systematic review provides a detailed overview of the effects of different types of physical exercise on improving NMJ in the elderly, providing scientific support for the timely intervention of muscle degeneration in the elderly by physical exercise, and providing help for the development of new therapeutic interventions in the future.